Biomarkers of lymph node metastasis in esophageal cancer - Wu, Ningzi; Cai, Junlan; Jiang, Junfei; Lin, Ye; Wang, Xiaoqing; Zhang, Weiguang; Kang, Mingqiang; Zhang, Peipei (Frontiers in Immunology, 2024)
Esophageal cancer (EC) is among the most aggressive malignancies, ranking as the seventh most prevalent malignant tumor worldwide. Lymph node metastasis (LNM) indicates localized spread of cancer and often correlates with a poorer prognosis, emphasizing the necessity for neoadjuvant systemic therapy before surgery. However, accurate identification of LNM in EC presents challenges due to the lack of satisfactory diagnostic techniques. Imaging techniques, including ultrasound and computerized tomography scans, have low sensitivity and accuracy in assessing LNM. Additionally, the existing serological detection lacks precise biomarkers. The intricate and not fully understood molecular processes involved in LNM of EC contribute to current detective limitations. Recent research has shown potential in using various molecules, circulating tumor cells (CTCs), and changes in the microbiota to identify LNM in individuals with EC. Through summarizing potential biomarkers associated with LNM in EC and organizing the underlying mechanisms involved, this review aims to provide insights that facilitate biomarker development, enhance our understanding of the underlying mechanisms, and ultimately address the diagnostic challenges of LNM in clinical practice. therapy (16,17). Consecutive stages of EC progression, from the precancerous, tumor-occurring to premetastatic niche (PMN) stages, are characterized by elements such as hypoxia, acidosis, and changes in the extracellular matrix (ECM), cytokines, inflammatory factors, and tumor-promoting cells that assist in immune avoidance and tolerance. Characteristic products in each stage can be promising biomarkers in LNM of EC. For example, EC cells could secrete IGF2 and elevate VEGF produced by tumor-associated fibroblasts via miR-29c in a p53-dependent manner, activating VEGFR1-positive bone marrow vascular progenitor cells in the tumor microenvironment (TME) and forming PMN (18). After irradiation, the upregulation of MiR-26b-5p in small extracellular vesicles (EVs) derived from dying ESCC cells promotes the proliferation and activation of myeloid-derived suppressor cells and macrophages. These cells suppress the PI3K/AKT pathway by targeting PTEN and eventually facilitate PMN formation (19). Therefore, the primary tumor-derived cells support PMN formation in LNs to aid the spread and colonization of cancer cells. Accordingly, several molecules are promising biomarkers for diagnosing, evaluating, and predicting LNM in EC and other cancer types. The molecular mechanisms